3D flow performance of mixed-flow pump using CFD approach - Zhou, Wei Dong. (2009)
This paper deals with a 3-D time-marching incompressible Navier-Stokes solver using the pseudo-compressibility technique to study the non-Newtonian flow field through mixed-flow water pump impeller. The applicability of the original code is validated by comparison with well published experimental and computational results. The pressure field solution is based on the pseudo-compressibility approach in which a time derivative pressure term is introduced into the mass conservation equation. Two non-Newtonian models based on Power-law and Casson relations are further included in the current code to predict the non-Newtonian flow through the same pump. The non-Newtonian results are compared with Newtonian ones in the laminar flow regime and it is found that the steady flow characteristics of the two fluids are rather similar. This indicates that the influence of non-Newtonian shear thinning behaviour might not be an important factor in determining the general flow patterns through a conventional large-scale mixed-flow water pump as the shear rates are high. However this will not be true for an actual-sized and viscous-dominant centrifugal pump.